2018
DOI: 10.1038/s41598-018-25123-2
|View full text |Cite
|
Sign up to set email alerts
|

Hsp90 inhibition as a means to inhibit activation of the NLRP3 inflammasome

Abstract: Once activated, the intracellular receptor NLRP3 assembles an inflammasome protein complex that facilitates the caspase-1-mediated maturation of IL-1β and IL-18. Inactive NLRP3 is guarded by a protein complex containing Hsp90. In response to stress stimuli, Hsp90 is released, and NLRP3 can be activated to promote inflammation. In this study, we blocked Hsp90 with geldanamycin and studied the fate of NLRP3 in human retinal pigment epithelial (RPE) cells. RPE cells play a central role in the development of age-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
97
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(101 citation statements)
references
References 56 publications
2
97
0
Order By: Relevance
“…From 3 h and up to 6 h from treatment, an impairment of intracellular traffic related to Rab proteins, already reported in choroideremia [51], was observed along with the alteration of autophagy and accumulation of proteins and damaged organelles. These events are typical of AMD [52] and are also enforced by inactivation of chaperone genes [53,54]. This scenario could reflect a strong reduction of macroautophagy (a catabolic cell survival system) and of a hybrid autophagy-phagocytosis-degradative pathway called LC3-associated phagocytosis (LAP) [55], which plays a critical role in visual pigment regeneration, as well as the complete degradation of phagosomes [56].…”
Section: Discussionmentioning
confidence: 99%
“…From 3 h and up to 6 h from treatment, an impairment of intracellular traffic related to Rab proteins, already reported in choroideremia [51], was observed along with the alteration of autophagy and accumulation of proteins and damaged organelles. These events are typical of AMD [52] and are also enforced by inactivation of chaperone genes [53,54]. This scenario could reflect a strong reduction of macroautophagy (a catabolic cell survival system) and of a hybrid autophagy-phagocytosis-degradative pathway called LC3-associated phagocytosis (LAP) [55], which plays a critical role in visual pigment regeneration, as well as the complete degradation of phagosomes [56].…”
Section: Discussionmentioning
confidence: 99%
“…We have recently examined ARPE-19 cells and observed that NLRP3 can be either secreted out of the cells or degraded by autophagy following inflammasome activation. 40 Additionally, extracellular components of the inflammasome have been detected previously from blood monocyte-derived macrophages, from the serum of patients suffering from cryopyrin-associated periodic syndrome, 41 and in the bronchoalveolar lavage taken from patients with chronic obstructive pulmonary disease and pneumonia. 42 Moreover, increased NLRP3 protein levels have been detected from the ocular surface epithelium of patients with non-Sjögren syndrome dry eye, 43 which could be evidence of the local accumulation of cellular NLRP3 protein in corneal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently reported similar findings in Hsp90-inhibited ARPE-19 cells where inactive NLRP3 was secreted out of the cells in addition to being degraded by autophagy. 40 Apart from IL-1β, the release of another inflammasomeregulated cytokine, IL-18, was studied here from UV-Bstimulated HCE cells. Although priming was needed to enhance the secretion of IL-1β, pro-forms of IL-18 appeared to be constitutively present in HCE cells.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple pathways, including inflammation and oxidative stress, have been reported in AMD pathogenesis. In vitro, stimulation of RPE cells with LPS + TCDD (oxidative stress and low-grade inflammation), TNFα (inflammatory stress) [117], IL-1α (prime inflammasome components) [129,149], IL-17A (signature cytokine of Th17 cells) [136], 4-hydroxyhexenal (unsaturated aldehydes) [139], sodium iodate (NaIO 3 ; oxidative stress) [142], oxidized-low density lipoprotein (ox-LDL; modified lipoprotein) [138,145], C5a (complement factor) [140], Aβ 1-40 [144,146], all resulted in elevated NLRP3 expression. Meanwhile, NLRP3 knockdown in A2E-treated ARPE-19 cells showed reduced ASC complex formation and IL-1β production [152].…”
Section: Nod-like Receptors In the Ocular Tissuesmentioning
confidence: 99%